(untitled) (Malaysian Management Journal, 2007)
Research has highlighted that organisational development (OD) is a complex issue as it requires the input of employees at all levels of an organisation. However, to obtain this is a challenge for organizations as the basic training and education offered by the organisations and experiences of the individuals on their own, and other factors such as fear and ignorance prevent such actions. For this purpose, other elements are also required. This research aims to identify and explain the usage of the elements that can encourage employees to contribute inputs necessary for OD. To achieve the aim, this research developed a conceptual framework based on the elements of understanding organisational roles, internal strengths, formal and informal discussion, and rational discourse. To illustrate the application of the framework in a real life setting, a case study approach that involved a large manufacturing organisation in Malaysia was employed. From this research, it was concluded that the future focus for the OD should be toward the development of staff members and creating suitable organisational culture and infrastructure so that knowledge sharing is promoted.